The Role of Speech Therapists in Olfactory Rehabilitation: A Short Report on Ten Cases of Total Laryngectomy - Michelle Passerini; Martina Da Re; Sonia Antoni; Cristina Pierluca; Giancarlo Tirelli; Vittorio Grill (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Introduction: Total Laryngectomy (TL) has to be performed in advanced hypopharyngeal or laryngeal cancer, with the consequence of both the loss of the vocal functions and the impairment or loss of smell and taste. Since less attention is turned towards the recovery of the olfactory function compared to the vocal rehabilitation, the Nasal Airflow-Induced Maneuver (NAIM) was proposed as a useful smell recovery method. In this short note, we report the results of the olfactory rehabilitation procedures by performing the NAIM technique in ten total laryngectomized patients with the evaluation of both the subjective olfactory detection and the olfactory discrimination, recognition and identification of odorous substances and we would emphasize the role of speech therapists in this rehabilitative procedure. Materials and methods: Ten total laryngectomized patients were proposed to undergo an olfactory rehabilitation cycle performed by speech therapists by employing the NAIM technique. The subjective olfactory detection was evaluate at three different time intervals during the rehabilitation cycle. The olfactory discrimination, recognition and identification capability was considered both during and 12 moths after the end of the rehabilitation treatment.  Results: The NAIM performed together with the speech therapist ameliorated significantly all olfactory functions.evidence and the functional recovery was confirmed 12 months after the end of the rehabilitation cycle, thus the role of speech therapists appears relevant in both the olfactory recovery and the maintenance of the regained olfactory capability.  Conclusion: The role of speech therapists should be aimed not exclusively towards the recovery of the vocal functions, but also towards the recovery of the olfactory functions. Speech therapists are able to adjust the original NAIM method to the specific need of each patient. Therefore, the role of speech therapists should be considered highly relevant to regain the olfactory function to allow again a good quality of life even after TL surgery.